Olfaction in raptors. Issue 3 (20th October 2019) - Potier, Simon
Abstract: Raptors from the orders Accipitriformes and Falconiformes have been considered to rely principally on vision. Historically, this assumption has led scientists to discount any possible sense of smell in these birds, until work on cathartid vultures indicated that these species at least rely on olfaction to find carrion. In this review I provide evidence that raptors in general have functional olfactory systems that they may use in a range of different contexts. Anatomical studies show that raptors have well-developed olfactory bulbs that are within the range of other bird species. Furthermore, all raptors studied have multiple functional olfactory genes, with, for instance, 283 olfactory genes in the Oriental honey buzzard, Pernis orientalis, of which 81.5% are functional. It has also been shown that some raptors species may functionally use olfactory cues to forage and, potentially, for communication. While further research is required, the available evidence suggests that olfaction may be a more important sensory modality in these birds than previously thought.